Evaluation of the Social Impact of the Development of the Mandalika Special Economic Zone on Local Communities - Maulana Alfateh Sahbana; Baiq Tutut Dwi Wiasti; Aldira Adsana Agustina; Nurfajar Hasanah; Denda Riratih; Alfat-H Maulana Muhammad (Journal of Governance and Spatial Planning, 2026)
The development of the Mandalika Special Economic Zone (SEZ) is a national strategic project aimed at promoting economic growth through tourism development; however, large-scale tourism development may also generate various social impacts on local communities. This study aims to evaluate the social impacts of the Mandalika SEZ development on local communities, particularly in terms of socio-economic conditions, socio-cultural changes, and land tenure. This research employs a qualitative approach with a case study design. Data were collected through interviews, field observations, and documentation involving local communities, community leaders, local government representatives, and area managers. Data analysis was conducted using the Social Impact Assessment (SIA) approach referring to the International Association for Impact Assessment (IAIA) to identify and evaluate the social consequences of the development process. The results indicate that the development of the Mandalika SEZ has created new economic opportunities for local communities, especially in tourism-related sectors, services, and small-scale businesses. However, these benefits have not been evenly distributed due to disparities in skills, education levels, and access to economic resources. In addition, the development has influenced social interactions, cultural practices, and land use patterns. Therefore, inclusive and participatory development policies are required to promote social equity and ensure socially sustainable tourism development in the Mandalika SEZ.